2019
DOI: 10.1371/journal.pone.0211022
|View full text |Cite
|
Sign up to set email alerts
|

Targeted HIV testing for male partners of HIV-positive pregnant women in a high prevalence setting in Nigeria

Abstract: BackgroundPartner HIV testing during pregnancy has remained abysmally low in sub-Saharan Africa, particularly in Nigeria. Males rarely attend antenatal clinics with their female partners, limiting the few opportunities available to offer them HIV testing. In this study, we evaluated the scale-up of the Healthy Beginning Initiative (HBI), a community-driven evidenced-based intervention to increase HIV testing among pregnant women and their male partners. Our objectives were to determine the: (1) male partner pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
2
13
2
Order By: Relevance
“…Reports elsewhere have indicated a higher prevalence among these groups (17). The higher prevalence of HIV among females (0.29%) compared to their male counterparts (0.14%) in this study is supported by reports elsewhere (18). Several reasons have been adduced for the higher prevalence among females, including their vulnerabilities, often associated with poor economic and sociocultural status, shy attitude towards sex education, and abhorrence of sex outside marriage culminating in restriction of young girls from access to sexual health and HIV services.…”
Section: Discussionsupporting
confidence: 84%
“…Reports elsewhere have indicated a higher prevalence among these groups (17). The higher prevalence of HIV among females (0.29%) compared to their male counterparts (0.14%) in this study is supported by reports elsewhere (18). Several reasons have been adduced for the higher prevalence among females, including their vulnerabilities, often associated with poor economic and sociocultural status, shy attitude towards sex education, and abhorrence of sex outside marriage culminating in restriction of young girls from access to sexual health and HIV services.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, 43% of 30 male partners interviewed reported never having tested for HIV. Without targeted interventions, proportions of men not/never tested for HIV are reported as approximately 97% in Nigeria [ 48 , 76 ] and between 35% and 95% in other African countries [ 77 ]. In addition to HIV knowledge, prior HIV testing facilitates male partner involvement in, and women’s access to PMTCT services [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, the prevalence of syphilis among MSM married to women was 17.9% [29]. Normally, partners found to be HIV- or HBV-positive ranged from 37.7 to 6.8% for infected pregnant women [30, 31]. However, the above prevalence varies by geographic regions and disease epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk for adverse events in women with syphilis concordant partners may be partly attributable to coinfection in couples. In addition, late ANC, high nontreponemal titers, and inadequate treatment may also lead to adverse outcomes [9, 30, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation